A first course in linear algebra - Kuttler, Kenneth; Lyryx Learning; Open Textbook Library; BC Open Textbook Project; BCcampus (Lyryx, 2014)
Linear Algebra: A First Course presents an introduction to the fascinating subject of linear algebra. As the title suggests, this text is designed as a first course in linear algebra for students who have a reasonable understanding of basic algebra. Major topics of linear algebra are presented in detail, with proofs of important theorems provided. Connections to additional topics covered in advanced courses are introduced, in an effort to assist those students who are interested in continuing on in linear algebra.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
Includes index.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Online version: Version 2014 Revision A; title from PDF (viewed on June 15, 2016).
Keywords: Algebras, Linear; Electronic books